2014
DOI: 10.11118/actaun200553040117
|View full text |Cite
|
Sign up to set email alerts
|

Energy analysis of various grassland utilisation systems

Abstract: RžONCA, J., MITRUŠKOVá, M., POZDÍŠEK, J., POSPIŠIL, R., MIČOVá, P., ŠTýBNAROVá, M., SVOZILOVá, M.: Energy analysis of various grassland utilisation systems. Acta univ. agric. et silvic. Mendel. Brun., 2005, LIII, No. 4, pp. 117-126 In 2003 and 2004 was carried out the energy analysis of the different types of permanent grassland utilization on the Hrubý Jeseník locality. There were estimated values of the particular entrances of additional energy. Energy entrances moved according to the pratotechnologies fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In these farms, very opportunities are to decrease the input energy without any reduction in the total output yield. Similar results is mentioned also in the past study by Ržonca et al (2005) who showed energy efficiency has decreased by increasing the input energies in grasslands.…”
Section: Econometric Model Estimation Of Cotton Productionsupporting
confidence: 90%
“…In these farms, very opportunities are to decrease the input energy without any reduction in the total output yield. Similar results is mentioned also in the past study by Ržonca et al (2005) who showed energy efficiency has decreased by increasing the input energies in grasslands.…”
Section: Econometric Model Estimation Of Cotton Productionsupporting
confidence: 90%